Implementasi Keperawatan Terapi Hipnosis Lima Jari Pada Orang Tua Yang Memiliki Anak Autism Spectrum Disorder - Pastari, Marta; Endriyani, Sri; Martini, Sri; Hisaan, Gina Khairaatun (JKM : Jurnal Keperawatan Merdeka, 2024)
Background: Autism is a serious neurobiological developmental disorder that occurs in children, causing problems for children to communicate and relate to their environment. Most parents have various emotional reactions when they find out that their child has autism. So it has a negative impact on parents both physically and psychologically, including parents who experience feelings of worry or anxiety (Mulyadi & Sutadi, 2014). Method: The design of this case study is descriptive with a nursing care approach that focuses on nursing implementation and evaluation. The subjects used in this case study were four patients with the same case and nursing problem, namely anxiety. The research location in this case study was at Nu_Kids Integrated Therapy, carried out for seven days for each patient, varying according to the date of visit from March to April 2023. Data collection methods used were interviews, observation, physical examination, implementation and assessment scales. The results of data collection are presented in the form of tables and narratives. Results: Before the researcher implemented five finger hypnosis therapy on clients, the researcher needed to build a relationship of mutual trust (BHSP) with the four clients in order to gain the trust of the clients. After BHSP, researchers used the SRQ questionnaire to determine the level of anxiety experienced by clients. It was found that Mrs. D value is 7 (there is a psychological problem of anxiety). To Mrs. S value is 6 (there is a psychological problem of anxiety). To Mrs. N value is 7 (there is a psychological problem of anxiety). To Mrs. NA value is 6 (there is a psychological problem of anxiety). The researcher then carried out the implementation of five-finger hypnosis nursing therapy for 7 days, once a day for 10-15 minutes, then the client would repeat it at home independently. After 7 days of implementing five finger hypnosis, the researcher assessed the client's response; where is Mrs. D can now speak relaxedly, his face is no longer tense, Mrs. S can concentrate again, Mrs. NA really understands and can carry out five finger hypnosis therapy without being facilitated or assisted by researchers, Mrs. N can now calm down and relax, and is starting to get used to relaxing when doing anything. Conclusion: The results of this study indicate that after being given the implementation of Five Finger Hypnosis Therapy, the four clients (100%) no longer experienced anxiety disorders with a score of Mrs. D and Mrs. N = five, Mrs. NA and Mrs. S = 4 (Score < 6 means there is no psychological problem of anxiety). So it can be concluded that five finger hypnosis therapy is effective in reducing anxiety.